Ali-A1 and TPL1 proteins interactively modulate awn development in wheat - Linyi Qiao; Tian Li; Shujuan Liu; Xueqi Zhang; Min Fan; Xiaojun Zhang; Xin Li; Zujun Yang; Juqing Jia; Ling Qiao; Zhijian Chang; Liuling Yan (Crop Journal)
The awn can contribute to photosynthesis and carbohydrates, enhancing grain yield in wheat. We mapped QAwn.sxau-5A, a major QTL for awn development in wheat (Triticum aestivum). This QTL was delimited to a 994-kb interval at the B1 locus on chromosome 5A, which included the candidate gene encoding a zinc finger protein (TraesCS5A01G542800) as an awn length inhibitor (ALI). The Ali-A1 allele for the awnless trait showed abundant sequence differences in the promoter regions compared to the ali-A1 allele for the long-awn trait. The results of the swap experiment on the promoters from the two ALI-A1 alleles showed that the two promoters caused a difference in the protein level, indicating the gene was regulated at the transcript level. However, the ali-A1 allele contained an SNP that caused a premature stop codon in its coding region, resulting in a truncated protein compared to the functional Ali-A1 protein. The Ali-A1 protein contained two ethylene-responsive element binding factor-associated amphiphilic repression (EAR) motifs, one at the N terminus (EAR-N) and the other at the C terminus (EAR-C), and they were involved in interactions with the wheat co-repressor protein TOPLESS (TPL1). The ali-A1 protein retained the EAR-N motif but lost the EAR-C motif, resulting in the attenuated ability to interact with TPL1. The tpl1 mutant produced a longer awn compared to the wild type. Ali-A1 repressed the transcription of two downstream genes, TaLRP-A1 and TaARF-B1, involved in endogenous auxin concentrations and auxin responses in wheat. We concluded that the awn length is regulated not only by the ALI-A1 gene at transcript levels but also by Ali-A1 and TPL1 at the protein level in wheat.